A Case Report of Incidental Primary Leiomyosarcoma of the Fallopian Tube and a Review of the Recent Literature. (May 2021) - Levine, Adam P.; Alexander, Sarah C.; Young, Martin; Arora, Rupali
Abstract : Primary leiomyosarcoma of the fallopian tube is a very rare neoplasm with descriptions limited to case reports. We present the case of a 46-yr-old woman with a history of renal transplantation in whom a primary leiomyosarcoma of the fallopian tube was identified incidentally following hysterectomy and bilateral salpingectomy undertaken for a uterine fibroid. The tumor demonstrated classic morphological and immunohistochemical features of a leiomyosarcoma. It appeared localized to the fallopian tube and was completely resected. Adjuvant therapy was not given but active surveillance initiated. After 14 mo of follow-up, there was no evidence of disease recurrence. We review cases from the past 20 yr with a focus on management and outcomes. Given the rarity of this disease, continued publication of case reports and the creation of a centralized case registry would be of benefit.